2016
DOI: 10.5897/ajar2016.11120
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of weeds in an Oxisol under no-tillage system

Abstract: In the global agribusiness, the herbicide use is a major problem for sustainable production, in this sense, it is necessary to better understand the interaction of weed species and floristic composition such as biodiversity indicators. The objective of this study was to analyze the spatial variability of weeds in an Oxisol under no-tillage system. Samples were taken in an area of 0.5 ha, in 50 sampling points with spacing of 5 m x 10 m. Data were analyzed by means of classical statistics, geostatistics, and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
4
7
0
Order By: Relevance
“…McIntosh, Shannon diversity, Simpson dominance, and Pielou equitability in the corn area; Simpson, McIntosh diversity, total diversity in soybean area; Simpson, McIntosh, Shannon diversity, total diversity, Simpson dominance, and Pielou equitability in the eucalyptus area; individuals trap -1 day -1 , jackknife richness, Simpson diversity, McIntosh diversity, total diversity, and Pielou equitability in the preserved Cerrado area; Simpson diversity, Shannon diversity, Simpson dominance, and Pielou equitability in the disturbed Cerrado; individuals trap -1 day -1 , Simpson, McIntosh, Shannon index, and Pielou equitability in the pasture area. Siqueira et al (2016) evaluating the variability of weeds in a no-tillage system obtained a pure nugget effect for the Shannon diversity index, the same occurred in the present study for millet, corn, eucalyptus, disturbed Cerrado, and pasture areas. The pure nugget effect indicates that 3 m spacing was not sufficient to detect spatial variability (Vieira, 2000).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…McIntosh, Shannon diversity, Simpson dominance, and Pielou equitability in the corn area; Simpson, McIntosh diversity, total diversity in soybean area; Simpson, McIntosh, Shannon diversity, total diversity, Simpson dominance, and Pielou equitability in the eucalyptus area; individuals trap -1 day -1 , jackknife richness, Simpson diversity, McIntosh diversity, total diversity, and Pielou equitability in the preserved Cerrado area; Simpson diversity, Shannon diversity, Simpson dominance, and Pielou equitability in the disturbed Cerrado; individuals trap -1 day -1 , Simpson, McIntosh, Shannon index, and Pielou equitability in the pasture area. Siqueira et al (2016) evaluating the variability of weeds in a no-tillage system obtained a pure nugget effect for the Shannon diversity index, the same occurred in the present study for millet, corn, eucalyptus, disturbed Cerrado, and pasture areas. The pure nugget effect indicates that 3 m spacing was not sufficient to detect spatial variability (Vieira, 2000).…”
Section: Resultssupporting
confidence: 84%
“…In general, changes in group abundance, diversity, and composition reflect disturbances of the ecosystem (Domínguez et al, 2014). Agricultural practices cause numerous changes in the composition and distribution of soil biota, directly affecting soil processes such as nutrient cycling, organic matter decomposition, porosity, and water infiltration (Vries et al, 2013;Wagg et al, 2014;Siqueira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In both sampling areas, it was possible to determine spatial distribution maps for dicotyledonous and monocotyledonous (Figures 2 and 3), as also observed by Chiba et al (2010) and Ferreira et al (2013). Kriging maps, in the two areas analyzed, represent a spatial ISSN 2166-0379 2020 distribution in spots or patches, confirmed by the dispersion index and the parameter k, as analyzed by Schaffrath et al (2007) and observed by Siqueira et al (2016). However, in area 01, Sida rhombifolia L. has a more uniform infestation throughout the landscape.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 66%
“…The theoretical, spherical and exponential models expressed better fit to the experimental semivariogram, whereas the dicotyledonous in area 01 fit better to the Gaussian model (Table 5). Comparable results were observed by Siqueira et al (2016) who obtained the best adjustments for the spherical, exponential and gaussian models. According to the classification of Cambardella et al (1994), the analyzed species presented strong degree of spatial dependence (DSD), except for dicotyledonous in area 01, which showed moderate DSD.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 56%
See 1 more Smart Citation